Poster Gender Diversity - Laure Humbert, Anne; Gunther, Elisabeth (Cranfield University, 2017)
This poster outlines the Gender Diversity Index and its main aims.
Keywords: 'Gender Difference'; 'gender composition'; 'Composite Measure'; 'Composite Indicators'; 'Team Effectiveness'; 'Performance assessment'; 'Higher Education'; 'Industry Economics and Industrial Organisation'; 'Statistics'; 'Statistics not elsewhere classified'; 'Gender studies'; 'Business and Management not elsewhere classified'; 'Human Resources Management'